2015
DOI: 10.1136/bmjopen-2014-007310
|View full text |Cite
|
Sign up to set email alerts
|

Familial transmission of chronic obstructive pulmonary disease in adoptees: a Swedish nationwide family study

Abstract: ObjectivesFamilial clustering of chronic obstructive pulmonary disease (COPD) is well established, but the familial risk of COPD has not been determined among adoptees. The aim was to determine whether the familial transmission of COPD is related to disease in biological and/or adoptive parents.DesignHistoric cohort study.Participants80 214 (50% females).MethodsThe Swedish Multi-Generation Register was used to follow all Swedish-born adoptees born in 1932–2004 (n=80 214) between 1 January 1964 and 31 December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Other factors, indicated as increasing the risk of development of COPD, are as follows: other than cigarette smoking form of tobacco use (e.g., cigar), marijuana, indoor pollution (such as from biomass cooking and heating in poorly ventilated dwellings), and occupational exposures to organic and inorganic dusts, chemical agents, and fumes [1]. Summarizing the contemporary knowledge, we should recognize the pathobiology of COPD as involving a complex interaction between several factors, including genetic vulnerability [5762]. …”
Section: Introductionmentioning
confidence: 99%
“…Other factors, indicated as increasing the risk of development of COPD, are as follows: other than cigarette smoking form of tobacco use (e.g., cigar), marijuana, indoor pollution (such as from biomass cooking and heating in poorly ventilated dwellings), and occupational exposures to organic and inorganic dusts, chemical agents, and fumes [1]. Summarizing the contemporary knowledge, we should recognize the pathobiology of COPD as involving a complex interaction between several factors, including genetic vulnerability [5762]. …”
Section: Introductionmentioning
confidence: 99%
“…One study provided prevalence of COPD in both biological and adoptive parents of people with COPD (both included in the pooled prevalence calculation). 58 Evidence of heterogeneity between the studies was found ( I 2 =98.8%; P <0.0001). A study by Silverman et al (1998) included a specific group of participants (severe early-onset COPD).…”
Section: Resultsmentioning
confidence: 91%
“…Of the eight studies, three studies reported on the prevalence of COPD in offspring of people with COPD (descendent approach, Table 2 ), with a total of 204 cases and 161 controls in two case–control studies and 5,054 participants in a cross-sectional study, 51 53 and five studies reported on the prevalence of a parental history of COPD in people with COPD (antecedent approach, Table 3 ), with 1,545 cases and 1,995 controls in four case–control studies and 80,214 participants in a cohort study. 54 – 58 None of the studies included in this review were primarily designed as prevalence studies, and all the studies included had a variable risk of bias when appraised using the prevalence appraisal checklist ( Table S2 ). 43 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations